Analisis Tingkat Partisipasi Masyarakat Terhadap Bencana Longsor di Kecamatan Karangtengah, Kabupaten Wonogiri - Prasetya, Mukti; , Dr. Ir. Imam Hardjono, M.Si (2016)
Karangtengah sub district located in Wonogiri, by BPBD Wonogiri map, this area has a high level of vulnerability to landslides. Therefore it is important for community to realize the threats that exist in the region. The purpose of this research is (1) .To comparison the level of public awareness in their respective areas against (2) Analysis level of public awareness and taken action against the landslides The method used in the research is survey interview by Propose random sampling based on highest level of vulnerability to landslides in Karangtengah The results of this research (1) The highest participation rates are in rural communities village of Ngambarsari, areas Jeblogan vilage and Temboro vilage have secondary enrollment rate, (2). Public participation research is done in two ways, effort and money, contribution of labor in the form of Mutal Coorporation, while cash donations from the government and other donors